Integrated Twin Tower (ITT) Based Learning to Think (LTT) Model to Enhance Scientific Creativity and Spiritual of students in the Early Childhood Islamic Education Department - Ratna Pangastuti; Ninik Fadhillah (Indonesia Approach Education, 2020)
The Indonesian National Qualification Framework in higher education requires universities to develop a curriculum so that students have superior competence with a variety of skills that are appropriate to the needs of the 21st century in the field of enhancing creative thinking skills. Expectations about the importance of scientific and spiritual creativity of Students of Early Childhood Islamic Education department based on the above literature review contradict the results of preliminary studies by researchers. The results of preliminary studies that there are complex problems that must be resolved immediately, and learning innovation and development of lecture devices that are specifically designed to develop scientific and spiritual creativity of students in the Early Childhood Islamic Education Department in UINSA is very needed. An alternative solution to the above problems that are offered by researchers is to develop an Integrated Twin Tower-based Learn to Think (LTT) learning model to enhance the scientific and spiritual creativity of students in the Early Childhood Islamic Education Department. This model was developed by correcting the weaknesses of the LTT model and adding an Integrated Twin Tower in each syntax based on the literature review that has been done before. Integrated Twin Tower is an innovative idea that has been developed at The Faculty of Tarbiyah and Teacher Training of UINSA with the foundation of thinking that the learning process cannot be separated between the core scientific fields of study and the Islamic values.